Slow modulation of ongoing activity in the auditory cortex during an interval-discrimination task - Juan M. Abolafia; Marina eMartinez-Garcia; Gustavo eDeco; Gustavo eDeco; Maria V Sanchez-Vives; Maria V Sanchez-Vives (Frontiers in Integrative Neuroscience, 2011)
In this study, we recorded the single unit activity from rat auditory cortex while the animals performed an interval-discrimination task. The animals had to decide whether two auditory stimuli were separated by either 150 or 300 ms, and go to the left or right nose-poke accordingly. Spontaneous firing in between auditory responses was compared in the attentive versus non-attentive brain states. We describe the firing rate modulation detected during intervals while there was no auditory stimulation. Nearly 18% of neurons (n=14) showed a prominent neuronal discharge during the interstimulus interval, in the form of a upward or downward ramp towards the second auditory stimulus. These patterns of spontaneous activity were often modulated in the attentive versus passive trials. Modulation of the spontaneous firing rate during the task was observed not only between auditory stimuli, but also in the interval preceding the stimulus. This slow modulatory components could be locally generated or the result of a top-down influence originated in higher associative association areas. Such a neuronal discharge may be related to the computation of the interval time and contribute to the perception of the auditory stimulus.